About the most sinful: mystical symbolism as a form of manifestation of eroticism in Medieval Europe - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
It is devoted to the analysis of mystical symbolism, inherent in medieval culture and characterized by a tendency to use very specific terminology and plots that are unexpected enough for the mystical context, which are distinguished by an apparent erotic coloration and are explained by the fact that eroticism as such is cast out by medieval culture beyond the traditional spheres of manifestation, that’s why his manifestation acquires bizarre and exotic forms, finding for himself a sphere of manifestation even inside of theological texts.
Keywords: mysticism; symbolism; manifestation; allegory; erotic terminology; marriage symbolism; eroticism; naturalism